Level of Digital Competence of Students in the First Year of Initial Teacher Training: A Look from the Variables of Gender and Educational Center; [Nivel de Competencia Digital de Estudiantes de Primer Año de Formación Inicial Docente: Una Mirada Desde Las Variables de Género y Centro Educativo] - Silva-Quiroz, J (Universidad de Sevilla, 2023)
The assessment of Digital Competence (DC) is a growing demand particularly among university students. It is particularly relevant for those who are training to become teachers, as the use of Digital Technologies (DT) in education requires adequate levels of DC. The objective of this study was to analyze the DC level of first-year initial teacher training (ITT) students from a Chilean public university and its possible relationship with the variables of gender and type of secondary education center. A quantitative methodology was used for a descriptive-inferential study, employing the assessment instrument DIGCOMP-PED [1], which evaluates CD according to the DIGCOMP framework. The study was applied to a sample of 448 first-year FID students in education courses at a Chilean public university. Descriptive and inferential analyses were performed through t-student and ANOVA tests. The results showed moderate DC levels. Additionally, significant differences were found for the two variables under study. Therefore, it is necessary that ITT programs diagnose the DC level of their students and develop strategies or complementary initiatives for a successful performance. Un adequate DC level during the first years of training favors the academic development of students and the future use of TD in their teaching practice. © 2023 Universidad de Sevilla. All rights reserved.